2018
DOI: 10.1186/s40478-018-0650-x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-beta and phosphorylated tau in post-mortem Alzheimer’s disease retinas

Abstract: In-vivo labeling of retinal amyloid-beta(Aβ) and tau has potential as non-invasive biomarker for Alzheimer’s disease (AD). However, literature on the presence of Aβ and phosphorylated tau (pTau) in AD retinas is inconclusive. We therefore assessed the presence of Aβ and pTau in post-mortem retinas in 6 AD and 6 control cases who donated brains and eyes to the Netherlands Brain Bank. Neuropathological diagnosis of AD was made according to NIA-AA criteria. Formalin fixed retinas were dissected in quadrants and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
205
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 144 publications
(222 citation statements)
references
References 34 publications
16
205
1
Order By: Relevance
“…The same might be true for the choroid. Similarly, amyloid deposits have been found on the retina in diseases such as Alzheimer's disease and cerebral amyloid angiopathy [21,22].…”
Section: Discussionmentioning
confidence: 93%
“…The same might be true for the choroid. Similarly, amyloid deposits have been found on the retina in diseases such as Alzheimer's disease and cerebral amyloid angiopathy [21,22].…”
Section: Discussionmentioning
confidence: 93%
“…Given that our group and others have demonstrated the existence of retinal Aβ deposits in AD patients [3,25,46,47,50], our next question was whether vascular PDGFRβ loss is associated with increased vascular Aβ deposition in postmortem retinas from MCI and AD patients. To this end, we studied retinal vascular Aβ 42 pathology in a cohort of age-and sex-matched human eye donors (n = 31, avg.…”
Section: Accumulation Of Retinal Aβ 42 In Blood Vessels and Pericytesmentioning
confidence: 99%
“…Among key findings were severe optic nerve and retinal ganglion cell (RGC) degeneration, thinning of the retinal nerve fiber layer (RNFL), glial stress, altered electroretinography responses, and vascular abnormalities [26,32,37,47,76]. Notably, the pathological hallmarks of AD-Aβ plaques and tauopathy-were further identified in the retina of AD patients, including early-stage cases [25,46,47,50]. Noninvasive high-resolution retinal imaging technologies such as fundus imaging, optical coherence tomography (OCT), as well as recently developed OCT angiography [42,62,72], retinal amyloid imaging [46][47][48], and retinal hyperspectral imaging [35,59] incentivize the use of feasible and inexpensive retinal imaging in the clinical setting to improve AD screening and monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The most well-known examples of biological differences between AD patients and healthy controls are widespread retinal ganglion cell losses, retinal nerve ber layer (RNFL) thinning and optic nerve degeneration (1)(2)(3)(4). At the biochemical level, amyloid-beta plaques have been observed in postmortem retina samples of AD patients (5), although others have failed to reproduce these results (6). In addition, tau accumulation was identi ed in postmortem retina samples of AD patients (6).…”
Section: Introductionmentioning
confidence: 99%
“…At the biochemical level, amyloid-beta plaques have been observed in postmortem retina samples of AD patients (5), although others have failed to reproduce these results (6). In addition, tau accumulation was identi ed in postmortem retina samples of AD patients (6). Previous studies also found soluble amyloidbeta in aqueous humor (7) and vitreous body (8) of cognitively healthy persons.…”
Section: Introductionmentioning
confidence: 99%